Randomised controlled feasibility trial of real versus sham repetitive transcranial magnetic stimulation treatment in adults with severe and enduring anorexia nervosa: the TIARA study. Issue 7 (16th July 2018) - Dalton, Bethan; Bartholdy, Savani; McClelland, Jessica; Kekic, Maria; Rennalls, Samantha J; Werthmann, Jessica; Carter, Ben; O'Daly, Owen G; Campbell, Iain C; David, Anthony S; Glennon, Danielle; Kern, Nikola; et al.
Abstract : Objective: Treatment options for severe, enduring anorexia nervosa (SE-AN) are limited. Non-invasive neuromodulation is a promising emerging intervention. Our study is a feasibility randomised controlled trial of repetitive transcranial magnetic stimulation (rTMS) in individuals with SE-AN, which aims to inform the design of a future large-scale trial. Design: Double-blind, parallel group, two-arm, sham-controlled trial. Setting: Specialist eating disorders centre. Participants: Community-dwelling people with anorexia nervosa, an illness duration of ≥3 years and at least one previous completed treatment. Interventions: Participants received 20 sessions (administered over 4 weeks) of MRI-guided real or sham high-frequency rTMS to the left dorsolateral prefrontal cortex in addition to treatment-as-usual. Outcomes: Primary outcomes were recruitment, attendance and retention rates. Secondary outcomes included body mass index (BMI), eating disorder symptoms, mood, quality of life and rTMS safety and tolerability. Assessments were conducted at baseline, post-treatment and follow-up (ie, at 0 month, 1 month and 4 months post-randomisation). Results: Thirty-four participants (17 per group) were randomly allocated to real or sham rTMS. One participant per group was withdrawn prior to the intervention due to safety concerns. Two participants (both receiving sham) did not complete the treatment. rTMS was safe and well tolerated. Between-group effect sizes of change scores (baseline to follow-up) were small for BMI ( d= 0.2, 95% CI −0.49 to 0.90) and eating disorder symptoms ( d =0.1, 95% CI −0.60 to 0.79), medium for quality of life and moderate to large ( d =0.61 to 1.0) for mood outcomes, all favouring rTMS over sham. Conclusions: The treatment protocol is feasible and acceptable to participants. Outcomes provide preliminary evidence for the therapeutic potential of rTMS in SE-AN. Largest effects were observed on variables assessing mood. This study supports the need for a larger confirmatory trial to evaluate the effectiveness of multi-session rTMS in SE-AN. Future studies should include a longer follow-up period and an assessment of cost-effectiveness. Trial registration number: ISRCTN14329415; Pre-results.